Map Analysis of The Pro-Con Arguments Against Permendikbud 30 Of Sexual Violence - Mariano Werenfridus; Iradhad Taqwa Sihidi; Krishno Hadi (Jurnal Ilmiah Ilmu Administrasi Publik, 2021)
The Ministry of Education, Culture, Research, and Technology of the Republic of Indonesia (Ministry of education and culture-Research and Technology) issued a Permendikbud No. 30 the Year 2021 on the Prevention and Handling of Sexual Violence (PPKS) in the College Environment. The policy raises pros - cons that are caused by the presence of the controversy the purpose and contents of the Culture of the. This study analyzes the perspectives of people through social media in response to the discharge of Permendikbud 30 of these. Descriptive qualitative methods as well as using secondary data collected through the social media Twitter. The direction of the study is based on Social Network Analysis (SNA) is a map of pro-contra to Permendikbud 30 about sexual violence that is obtained through the Drone Emprit Publications. The scope of the study discusses 1). The trend and the Volume of Pro - Counter Culture 30, 2). SNA Permendikbud 30 (Cluster Pro and Cluster Counter), 3) SNA “Bridge” Permendikbud 30, 4). Clique/The Huddle, 5). Hashtag Pros and Cons Permendikbud 30, 6). Top Influencers: Pro - Cons Permendikbud 30, 7). The analysis of the emotions of cluster Pro - Cons. The results of the analysis show that the issuance of Permendikbud 30 raises pro-cons and war the hashtags that are dominated by the group pro. Thus, this study based on the analysis of the data shows that the enthusiasm of the community in social movements in the form of a response to government policy is very high either a stronghold of the pro or the stronghold of the counter.